2018
DOI: 10.1038/s41598-018-20108-7
|View full text |Cite
|
Sign up to set email alerts
|

Aging extension and modifications of lipid metabolism in the monogonont rotifer Brachionus koreanus under chronic caloric restriction

Abstract: To examine the interrelationship of aging extension and modification of lipid metabolism under chronic caloric restriction (CCR; reduced concentration of the green algae Tetraselmis suecica) in the monogonont rotifer Brachionus koreanus, we assessed life cycle parameters, fatty acid composition, and expression of sirtuin and genes related to lipid metabolism. B. koreanus in the 5% T. suecica group showed an increased life span but decreased reproduction. Based on this finding, we chose 5% T. suecica for furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 48 publications
(67 reference statements)
1
4
0
1
Order By: Relevance
“…However, at lower concentrations (0.1, 0.5, and 1 μg/L), TBT did not induce significant changes compared to the control. In general, lifespan and reproduction show an inverse relationship in rotifers under moderately toxic conditions, which aligns with the costs of reproduction hypothesis. As one of the survival strategies, rotifers extended their lifespan under moderate toxic environment for future reproduction. However, in this study, severe toxic effects were observed only at 5 μg/L TBT, indicating that the 5 μg/L TBT exposure condition is so toxic that B.…”
Section: Discussionsupporting
confidence: 73%
“…However, at lower concentrations (0.1, 0.5, and 1 μg/L), TBT did not induce significant changes compared to the control. In general, lifespan and reproduction show an inverse relationship in rotifers under moderately toxic conditions, which aligns with the costs of reproduction hypothesis. As one of the survival strategies, rotifers extended their lifespan under moderate toxic environment for future reproduction. However, in this study, severe toxic effects were observed only at 5 μg/L TBT, indicating that the 5 μg/L TBT exposure condition is so toxic that B.…”
Section: Discussionsupporting
confidence: 73%
“…65,66 However, the actual roles of HSP12 and POR1 in the copper resistance and copper uptake ability of S. cerevisiae are yet not revealed. A lower level of intracellular copper and the in turn upregulation of metal transporters were reported in S. cerevisiae under the calorie restriction, 67 while reduction in the triacylglycerol level was found in the monogonont rotifer Brachionus koreanus under the chronic caloric restriction, 68 implying the possible connection of lipid metabolism with copper metabolism. In this study, no obvious differences in copper resistance and transcription levels of HSP12 or POR1 were observed between the mutant H247 and the reference strain Cu-5.…”
Section: ■ Discussionmentioning
confidence: 92%
“…Although diet may have had an influence on the ability of female copepods to defend against harmful UV irradiation in our study, it is unlikely that the observed effects herein are due to diet, provided that all females were supplied ad libitum access to the same algae throughout the study (see Lee et al, 2018 for how caloric restriction may influence the life history of aquatic organisms). Furthermore, UV radiation is necessary for endogenous vitamin D production; an induced increase in vitamin D via UV irradiation in Daphnia has been shown to increase fecundity (Connelly et al, 2015).…”
Section: Discussionmentioning
confidence: 94%